Development and Nutrition of Soybeans with Macronutrients Deficiencies - Firmato de Almeida, Thiago Batista; Flores, Rilner Alves; Almeida, Hilario Junior de [UNESP]; Prado, Renato de Mello [UNESP]; Carvalho Maranhao, Deyvid Diego; Politi, Lucas Sanches [UNESP] (Taylor & Francis Inc, 2017)
Soy is to one of the main crops in the world. However, there are aspects related to its management that should be explained, especially regarding its mineral nutrition, because a proper nutritional balance is associated with productivity levels. The objective of this study was to evaluate the accumulation of nutrients in the tissues related to the deficiency of nutrients and its effects on plant development. In addition, nutritional disorder symptoms were evaluated according to the deficiency of macronutrients. For this, seven treatments were evaluated. They comprised a complete nutrient solution followed by deficiency of nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), and sulfur (S) in a completely randomized design with three replications. Plant height, number of leaves, leaf area, stem diameter, relative chlorophyll content, and production of dry matter of soybean plants were evaluated. The deficiency of any macronutrient affects biometric variables, especially the production of dry matter. The nutrients that limited the most the production of dry matter were Ca>N>K>Mg>P>S. With the exception of S, all other macronutrients, when suppressed, caused nutritional disorder symptoms. The plants presented an accumulation of K>N>Ca>P>Mg>S in leaves. In the present study, soybean plants had a high nutritional requirement of K followed by N. This requires care in the development of fertilization programs in view of the essential roles these nutrients play in the life cycle of plants.Abbreviations: N_Nitrogen; P_Phosphorus; K_Potassium; Ca_Calcium; Mg_Magnseium; S_Sulfur; DM_Dry matter; NL_number of leaves; H_plant height; SD_stem diameter; RCI_Relative chlorophyll index; AP_Aerial part; R_Roots; EP_Entire plant; DMS_significant mean difference; CV_Coefficient of variation; pH_hydrogen potential; NaOH_sodium hydroxide; HCl_hydrochloric acid.
Keywords: Glycine max; nutritional disorder; plant nutrition